ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR IKAN KEDONGANAN KECAMATAN KUTA KABUPATEN BADUNG - Saragih, Vildya Lasnt Elyas; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.06.TAHUN.2022, 2022)
Based on data on fishery production in Bali Province in 2018-2020, Badung Regency experienced a very large decrease in production, so that it affected the income of fish traders and fishermen at the Kedonganan Fish Market. This study aims to examine the factors that influence the income of traders at the Kedonganan Fish Market, Kuta District, Badung Regency through Confirmatory Factor Analysis and Multiple Linear Regression analysis. The emphasis in this research is on capital, length of business, working hours, survival strategies, and income. This research is a research that uses qualitative and quantitative approaches that are associative. Simultaneous research results show that capital, length of business, working hours, and survival strategies have a significant effect on the income of traders at the Kedonganan Fish Market, Kuta District, Badung Regency. Partially shows that capital and length of business have a positive and significant effect on the income of traders at the Kedonganan Fish Market, Kuta District, Badung Regency. Working hours and survival strategies partially show that they have no effect on the income of traders at the Kedonganan Fish Market, Kuta District, Badung Regency.